Strict and uniform Shariah screening methodologies in selected Asian countries in comparison with the United States - Kasi, Umayal; Muhammad, Junaina (Macrothink Institute, 2016)
This paper focuses mainly on the Shariah screening methodologies for Shariah-Compliant firms. This paper compares the Shariah screening methodologies which are used in selected Asian countries and the United States, a ‘powerhouse’ nation. In order to include the analysis of the new benchmark introduced in Malaysia as part of this study, the timeline used in this paper is from November 2013 until November 2014. It can be found that there are similarities and differences between the various Shariah screening methodologies in all the 5 countries, in terms of feasibility, duration, economic viability and fund requirements. It also appears that the Shariah screening methodologies implied in the United States is far more stringent than those implied in the selected Asian countries. On the whole, the results point towards the possibility of generalising the implementation of strict and uniform Shariah screening methodologies within all the country-specific Shariah Indices amongst Muslim nations, globally.